Waste heat-driven desalination systems: Perspective. (15th October 2020) - Olabi, A.G.; Elsaid, Khaled; Rabaia, Malek Kamal Hussien; Askalany, Ahmed A.; Abdelkareem, Mohammad Ali
Abstract: This perspective discusses the utilization of waste heat (WH) for desalination with focus given to desalination processes that can be fully driven by WH, either directly as thermal energy, for thermally-driven desalination processes, or indirectly to other desalination processes using the appropriate WH recovery technology. The perspective focus as well on the utilization of WH for driving emerging desalination processes such as humidification dehumidification HDH, membrane distillation MD, and adsorption desalination AD. The discussion extends to the utilization of WH for conventional thermal desalination technologies such as multi-stage flash distillation MSF and multiple-effect distillation MED. The discussion follows on utilizing WH for other mechanically- and electrically-driven desalination processes such as reverse osmosis RO and electrodialysis reversal EDR and capacitive deionization CDI as well. The perspective concludes that WH represents a reliable and sustainable energy source with proven technical, economic, and environmental potentials to drive different desalination processes. The utilization of WH maximizes the energy efficiency of fuel utilization, and lowers the associated environmental impacts and carbon footprint. Graphical abstract: Image 1 Highlights: 50% of the energy is wasted as heat. Waste heat has been successfully utilized to drive desalination processes. Emerging desalination process has a higher potential to utilize waste heat. Waste heat utilized in desalination result in significant cost. Waste heat utilization substantially reduce GHGs emissions of desalination.